Impact of first-line FOLFIRINOX versus Gemcitabine/Nab-Paclitaxel chemotherapy on survival in advanced pancreatic cancer: Evidence from the prospective international multicentre PURPLE pancreatic cancer registry. (October 2022) - Santucci, Jordan; Tacey, Mark; Thomson, Benjamin; Michael, Michael; Wong, Rachel; Shapiro, Julia; Jennens, Ross; Clarke, Kate; Pattison, Sharon; Burge, Matthew; Zielinski, Rob; Nikfarjam, Mehrdad; et al.
Abstract: Background: First-line palliative chemotherapy regimens in advanced pancreatic ductal adenocarcinoma (PDAC) have not been compared in head-to-head phase III randomised controlled trials (RCT). Data on optimum first-line treatment and subsequent sequencing is lacking. Objective: To compare overall survival (OS) between first-line treatment regimens in a real-world population to determine if an optimal therapeutic sequence is associated with survival benefit. Methods: A retrospective analysis of prospectively collated data from the Australasian PURPLE pancreatic cancer registry was undertaken. Findings: From 2016 to 2020, of 1551 pancreatic cancer patients, 615 received palliative-intent chemotherapy. Patients with early-stage resected disease without recurrence (n = 369), radiotherapy alone (n = 43), received supportive care alone (n = 458) or had less than 3 months follow-up (n = 66) were excluded. Median OS was comparable between patients receiving first-line Gemcitabine/Nab-Paclitaxel (n = 376) and those receiving FOLFIRINOX (n = 73) (11.3 versus 12.3 months, P = 0.37), with 38% proceeding to second-line chemotherapy which was associated with longer mOS compared to first-line treatment alone (17.4 versus 8.2 months, P < 0.001). With second-line treatment following prior FOLFIRINOX (n = 29) or Gemcitabine/Nab-Paclitaxel (n = 101), mOS did not differ significantly (17.3 versus 15.9 months, P = 0.92), respectively, whilst median progression-free survival was longer with prior FOLFIRINOX (5.2 versus 2.9 months, P = 0.03). Conclusion: There was no significant difference in overall survival between either first-line chemotherapy choice, despite patients receiving FOLFIRINOX being younger, fitter, and more likely to have localised disease. However, FOLFIRINOX was associated with delayed progression. In the absence of phase III RCT data, clinicians should be comfortable using either Gemcitabine/Nab-Paclitaxel or FOLFIRINOX as first-line therapy in advanced PDAC. Highlights: Analysis of optimal therapeutic sequencing in advanced pancreatic cancer (n = 615). 1st-line FFX efficacy comparable to GEM-P (mOS 11.3 versus 12.3 months P = 0.37). Longer mOS with 2nd-line chemotherapy versus 1st-line only (17.4 versus 8.2 months P < 0.001). 2nd-line 5FU versus GEM-based treatment mOS similar (17.3 versus 15.9 months P = 0.92).